Self-Employment in Chile, Long Run Trends and Education and Age Structures Changes - Puentes, Esteban (Estudios de Economía, 2016)
This paper studies long-term trends of self-employment in Chile. Self-employment is associated with poor job conditions, vulnerability, and instability or informal labor market. Contrary to what is expected, self- employment level does not respond to macroeconomic variables. Using forty-one cross sections of the longest Employment Survey available, we show that there is little correlation of the economic cycle with variations in self-employment. Cohort effects are also unimportant. In fact, age is the most important predictor of self- employment; older people are more likely to be self-employed. In addition, we performed a decomposition of changes in self-employment on changes in coefficients, which are a measure of the returns to individual characteristics, and on changes in characteristics. The results indicate that self-employment should have decreased given the changes in individual characteristics, but was prevented by changes in coefficients. We also find indirect evidence that these changes in parameters are not correlated with macroeconomic variables. Finally, the changes in individual characteristics, such as education and age, and changes in their coefficients account for most of the changes in self-employment.